Regulacja ochrony praw dziecka w Ustawie Republiki Litewskiej o etyce badań biomedycznych - Buzytė, Miglė; Balsienė, Janina (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The legal regulation of children’s rights in clinical research in the Republic of Lithuania, related problems and possible suggestions are considered in the article. The Law on Ethics of Biomedical Researchof the Republic of Lithuania is amajor national law regulating the legal relations arising in biomedical research. This article deals with the Republic of Lithuania’s Law on Ethics of Biomedical Research and provides biomedical test conditions: biomedical scientific researchand practical value; the documents of competent authorities entitled to perform biomedical research; and other legal acts that do not preclude carrying out ofbiomedical research; the protection of rights of the children participating in biomedical research and the confidentiality of information on research. Attention is paid to problematical issues regarding the consent of aminor to take part in clinical trials. The article proves that the requirement to obtain consent from the Children’s Rights Protection Agency does not guarantee any additional protection for aminor. The current draft Law on Ethics of Biomedical Research is also being discussed.
Keywords: Litwa; prawa dziecka; ochrona praw człowieka; prawo etyczne badań biomedycznych